2003
DOI: 10.1111/1468-0432.00213
|View full text |Cite
|
Sign up to set email alerts
|

A Privileged Pole? Diversity in Women's Pay, Pensions and Wealth in Britain

Abstract: Is gender on its own becoming redundant in the analysis of employment experiences? There is a growing interest in economic diversity amongst women within the social sciences, with commentators suggesting, firstly, that a polarization in women's labour market experiences is occurring. Secondly, economic diversity amongst women may even be so distinct that a privileged pole is faring substantially better in wage and occupational terms than most men. This article uses data from the Family Resources Survey to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
(22 reference statements)
1
23
0
Order By: Relevance
“…Given that women are more likely to be low paid (Saari 2013;Warren, 2003), we see a higher proportion of women being excluded (Meyer, 2014). However, even for those enrolled there are concerns that the value of the pension will not to deliver sustainable retirement incomes (PWC, 2012;Uren 2013).…”
Section: Gender Blindness and Auto-enrolmentmentioning
confidence: 94%
“…Given that women are more likely to be low paid (Saari 2013;Warren, 2003), we see a higher proportion of women being excluded (Meyer, 2014). However, even for those enrolled there are concerns that the value of the pension will not to deliver sustainable retirement incomes (PWC, 2012;Uren 2013).…”
Section: Gender Blindness and Auto-enrolmentmentioning
confidence: 94%
“…During the last recessionary period pay gaps were larger. Whilst there are greater numbers of women in high-paid managerial and professional positions with access to private pension schemes in many countries than in previous recessions, polarisation between pension prospects of the lowest and highest paid women are increasingly apparent and women still tend to have lower wages than men (Warren, 2003). Previous explanations of the impact of recessions on women's employment by Rubery (1988) indicated that women represented a flexible reserve or buffer, to be drawn into the labour market in upturns and expelled in downturns, especially in female-dominated sectors, but that during recessions there is a more significant demand for cheaper forms of labour (which often does not involve private pension opportunities).…”
Section: Women's Employment and The Financial Crisismentioning
confidence: 99%
“…Not only are there clear gender differences, but also occupational class differences, in part-time working in the UK (e.g., Lyonette, Baldauf, & Behle, 2010 ;Warren, 2003 ). Only 23 % of higher professional and managerial women work part-time, compared with 58 % of women in semi-routine occupations and 64 % in routine occupations 1 (LFS, Oct-Dec 2013).…”
Section: The Current Status Of Part-time Work In the United Kingdom (Uk)mentioning
confidence: 99%
“…However, extensive research has shown that most part-time work is offered in lower-level jobs, with lower training and promotion prospects than fulltime jobs (e.g., Hoque & Kirkpatrick, 2003 ). Part-time work has also been consistently shown to pay less than similar full-time work (Connolly & Gregory, 2009 ;Warren, 2003 ).…”
Section: Introductionmentioning
confidence: 99%